2010
DOI: 10.1182/blood-2009-07-234211
|View full text |Cite
|
Sign up to set email alerts
|

Human γδ T lymphocytes induce robust NK cell–mediated antitumor cytotoxicity through CD137 engagement

Abstract: IntroductionNatural killer (NK) cells contribute to innate immune responses against virally infected and neoplastic cells. 1 NK cells usually recognize and attack tumor cells that lack major histocompatibility complex (MHC) class I. 2 Our previous studies in murine tumor models clearly demonstrated that gamma delta (␥␦) T lymphocytes play an important role in the regulation of antitumor NK-cell function. 3 Specifically, we have shown that ␥␦ T lymphocytes are required for the antitumor activity of NK cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
192
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(202 citation statements)
references
References 33 publications
7
192
3
Order By: Relevance
“…For example, recent data have demonstrated that cd T lymphocytes can induce robust natural killer cellmediated anti-tumour cytotoxicity. 22 Additionally, increasing evidence has demonstrated that cd T cells play an important role in the cross-talk between innate and adaptive immunity. cd T cells actively regulate the adaptive immune response through interactions with antigen presenting cells, such as dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent data have demonstrated that cd T lymphocytes can induce robust natural killer cellmediated anti-tumour cytotoxicity. 22 Additionally, increasing evidence has demonstrated that cd T cells play an important role in the cross-talk between innate and adaptive immunity. cd T cells actively regulate the adaptive immune response through interactions with antigen presenting cells, such as dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism might also enhance this phenomenon in vivo because CTX may exert its antitumor effects via pathways unrelated to EGFR‐targeting, such as through antibody‐dependent cell cytotoxicity (ADCC) 37. ZOL is also reported to increase the number of γδT cells, which are thought to activate ADCC 38. The evidence suggests that both reagents may synergistically enhance ADCC activity.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the tumor necrosis factor receptor (TNFR) family 1 and, upon crosslinking of the receptor by natural or artificial ligands, is endowed with co-stimulatory properties for T-cell activation. 2,3 Tissue distribution is broader than originally described, as CD137 has also been found to decorate activated natural killer (NK) cells, 4,5 B cells, 6 dendritic cells (DCs), 7 myeloid precursors, 8 mastocytes, 9 and tumor capillary endothelial cells. 10 There is only one described ligand, namely CD137L or 4-1BBL, 11 which acts as an agonistic moiety that crosslinks 4-1BB giving rise to activation signals.…”
Section: Introductionmentioning
confidence: 90%